Development of UI/UX Based Microlearning to Prevent Misconception in Physics Learning with Computational Thinking Approach - Siti Nur Ayu; Asti Aulia Sari; Zidny Manaasika (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2025)
Physics learning is often faced with the challenge of the complexity of abstract concepts, potentially causing misconceptions in students. This research aims to develop microlearning learning media based on User Interface (UI) and User Experience (UX) to prevent misconceptions in thermodynamics material, with a computational thinking (CT) approach. This research uses the Research and Development (R&D) method that adapts the Borg and Gall model, but is limited to the product design stage. The media was developed through the stages of identifying potential and problems, literature review, and prototype design using the Figma platform. The development results show that UI/UX-based microlearning can present material in a concise, interactive, and adaptive manner in accordance with the learning characteristics of the digital generation, and support the formation of algorithmic mindset through concept decomposition and visualization. Although this research has not involved empirical effectiveness testing, the media design shows significant potential in improving concept understanding and preventing misconceptions. Further research is recommended to complete the R&D stage to test the impact on physics learning outcomes as a whole.